One year monitoring by FTIR of γ-irradiated multilayer film PE/EVOH/PE. (August 2016) - Gaston, Fanny; Dupuy, Nathalie; Marque, Sylvain R.A.; Barbaroux, Magali; Dorey, Samuel
Abstract: The multilayer films made of polyethylene/polyethylene-co-vinyl alcohol/polyethylene are γ-irradiated for biopharmaceutical and biotechnological applications. The radiations generate changes in the polymer films. In this study, we focused on the modifications produced on the surface of materials by Fourier transformed infrared (FTIR) spectroscopy combined with chemometric treatments. Principal component analysis (PCA) allows the ordering of the surface modifications according to absorbed doses and the natural ageing. Results show the rising of the acid band and the variation of unsaturated compounds. Graphical abstract: Highlights: γ-ray sterilization of single-use plastic bags for biotechnology and biopharmaceutical applications. Use of ATR-FTIR spectroscopy to monitor the modifications of γ-irradiated polymers over time. Interpretation and highlighting of slight spectral variations after multiple absorbed doses using chemometric methods.